Indoor PM10 Concentration and Respiratory Diseases on Children in Area Around Limestone Combustion - Maharani Pulungan, R (KnE Life Sciences, 2019)
The purpose of this study was to analyze the relationship between indoor PM10 concentration and respiratory diseases in infants/young children. The study design was cross-sectional, conducted on 130 infants/young children. PM10 and data of other variables collected through measurement, interviews, and observation. The results showed dominant factor causing respiratory diseases in infants/young children was indoor PM10 (4.92; 2.25-10.74), after controlled ventilation the house (2.62; 1.18-5.79), type of wall (2.33; 1.10-4.95), humidity (2.35; 1.10-5.04), temperature (2.44; 1.15-5.18), smoking family members (5.40; 1.74-16.75), and maternal education (2.86; 1.16-7.07). Risk analysis showed that at-risk group (indoor PM10 concentrations>70 μg/m3) was 13.42 times to have the risk experiencing respiratory diseases than the non-risk group (indoor PM10 concentrations ≤ 70 μg/m3). Keywords: respiratory diseases, indoor particulate matter (PM)10